Learning Methods in English Class - Alicia Syabina; Rossy Annisa; Ulfa Lifia Bahri; Emeliya Sukma Dara (Yayasan Zia Salsabila, 2022)
English is a language for writing and speaking. To comprehend the meaning of information, thoughts, and feelings and to use language to advance science, technology, and culture is to comprehend and express communication. If you want to keep up with how the world is changing, you need to know and understand English. This study looked at how English class learning methods and facilities affected students' motivation to learn more about art and culture. The results show that better facilities improve students' motivation. Students will be able to learn more effectively and more easily if the appropriate method is chosen. In addition, the students' motivation to learn can be influenced and bolstered by the availability of a quality learning facility and the effective implementation of the learning method.